Penyuluhan Komunikasi, Informasi Dan Edukasi (Kie) Kesehatan Reproduksi Pada Remaja Kelas 6 Sd Negeri 03 Kabawetan - Hasibuan, Mutiara; Situmorang, Anggita; Siagian, Taruli; Murwati, Murwati; Wulandari, Wulandari; Azissah, Danur; Rohani, Tuti (Jurnal Kewirausahaan dan Bisnis, 2025)
The period of physical maturation in adolescent girls is marked by the start of menstruation, while in adolescent boys it is marked by experiencing wet dreams. Reproductive health is a condition of physical, mental and social health related to the reproductive system, its functions and processes: Reproductive health is not only free from disease or weakness. Reproductive health is important to maintain reproductive organs. Reproduction is the process of living creatures producing offspring to maintain the survival of their species. Reproduction in humans differs in structure and function in men and women. Adolescence is the process of a person experiencing the development of all aspects from childhood to adulthood. The transition from childhood to adulthood is often called puberty. Puberty is a time when teenagers experience sexual maturity and their reproductive organs begin to function. Objective: at the end of the counseling process, all grade 6 students of SD Negeri 03 Kabawetan, Kepahiang Regency can understand and understand about communication, information, and education (KIE) of reproductive health in adolescents